STRATIGRAPHIC EVIDENCE FOR MILLENNIAL-SCALE TEMPORAL CLUSTERING OF EARTHQUAKES ON A CONTINENTAL-INTERIOR FAULT: HOLOCENE MISSISSIPPI RIVER FLOODPLAIN DEPOSITS, NEW MADRID SEISMIC ZONE, USA - Holbrook J.; Autin W.J.; Goble R.J.; Marshak S.; Rittenour T.M. (My University, 2006)
The earthquake cycles that characterize continental-interior areas that are far from active plate boundaries have proven highly cryptic and difficult to resolve. We used a novel paleoseismic proxy to address this issue. Namely, we reconstructed Holocene Mississippi River channels from maps of floodplain strata in order to identify channel perturbations reflective of major displacement events on the high-hazard and mid-plate Reelfoot thrust fault, New Madrid seismic zone, U.S.A. Only three discrete slip events are currently documented for the Reelfoot fault (~ AD 900, ~ AD 1450, and AD 1812). This study extends this record and, thus, illustrates the utility of stratigraphic proxies as paleoseismic tools. We concurrently offer here some of the first quantified response times for tectonically induced channel pattern changes in large alluvial rivers. We identified at least two cycles of pervasive meandering that were interrupted by channel-straightening responses occurring upstream of the Reelfoot fault scarp. These straightening responses initiated at 2244 BC +/- 269 to 1620 BC +/- 220 and ~ AD 900, respectively, and each records initiation of a period of Reelfoot fault slip after millennia of relative tectonic quiescence. The second (or New Madrid) straightening response was triggered by the previously known ~ AD 900 fault slip event, and this initial low sinuosity has been protracted until the modern day by the latter ~ AD 1450 and AD 1812 events. The first (or Bondurant) straightening response began a period of several hundred to ~ 1400 years of low river sinuosity which evidences a similar period of multiple recurrent displacement events on the Reelfoot fault. These Bondurant events predate the existing paleoseismic record for the Reelfoot fault. These data offer initial evidence that slip events on the Reelfoot fault were temporally clustered on millennial scales and, thus, offers the first direct evidence for millennial-scale clustering of earthquakes on a continental-interior fault. This carries additional ramifications. Namely, faults that have been quiescent and non-hazardous for millennia could re-enter an enduring period of recurrent hazardous earthquakes with little warning. Likewise, the Reelfoot fault also reveals evidence of temporal clustering of earthquakes on short-term cycles (months), as well as evidence for longer-term reactivation cycles (104-106 years). This introduces the possibility that temporal clustering could be hierarchical on some continental-interior faults. © 2006 Elsevier B.V. All rights reserved.
Keywords: FAULT; FLUVIAL; INTRAPLATE TECTONICS; MISSISSIPPI RIVER; NEW MADRID SEISMIC ZONE; PALEOSEISMOLOGY; STRATIGRAPHIC PROXY; TEMPORAL CLUSTERING; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен